Filosofía africano-brasileña: ancestralidad, encantamiento y educación afro-referenciada (2022)
Ancestrality is an epistemological and political reading of the black African tradition recreated in Brazil. An analytical category with political and epistemological density that takes place in time and space, and gives rise to enchantment. It is an experience that transforms, from itself, into a relationship with the collective, a relationship of praxis, thinking-doing, without separating aesthetics from ethics and politics from culture. These are concepts that support us so that we can dialogue with African philosophies, producing an Afro-Brazilian philosophy. Thinking-creating-philosophizing-educating in dialogue with all knowledge, reflecting from our writings, our belonging, articulating our subjective and collective being-in-the-world. It is a complex and creative relationship with our being-in-the-world. Involvement with education for liberation.